Epidemiological features of esophageal cancer. Squamous cell carcinoma versus adenocarcinoma - Henry, Maria Aparecida Coelho de Arruda [UNESP]; Lerco, Mauro Masson [UNESP]; Ribeiro, Priscila Watson; Rodrigues, Maria Aparecida Marchesan [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2014)
PURPOSE: To analyze the epidemiological features of patients with esophageal cancer according to the histopathological types: squamous cell carcinoma or adenocarcinoma. METHODS: A total of 100 patients with esophageal cancer, being 50 squamous cell carcinomas and 50 adenocarcinomas were analyzed for demographics, nutritional factors, lifestyle habits, benign pathological conditions associated, like Barrett's esophagus and megaesophagus, tumor stage and survival rates. The nutritional factors evaluated included body mass index, percent weight loss, hemoglobin and albumin serum levels. RESULTS: Esophageal cancer occurred more often in men over 50 years-old in both histological groups. No significant differences on age and gender were found between the histological groups. Squamous cell carcinoma was significantly more frequent in blacks than adenocarcinoma. Alcohol consumption and smoking were significantly associated with squamous cell carcinoma. Higher values of body mass index were seen in patients with adenocarcinoma. Barrett's esophagus was found in nine patients (18%) with adenocarcinoma, and megaesophagus in two patients (4%) with squamous cell carcinoma. The majority of patients were on stages III and IV in both histological groups. The mean survival rates were 7.7 ± 9.5 months for patients with squamous cell carcinoma and 8.0 ± 10.9 months for patients with adenocarcinoma. No significant differences on tumor stage and survival rates were detected between the histological groups. CONCLUSION: Epidemiological features are distinct for the histopathological types of esophageal cancer. Squamous cell carcinoma is associated with black race, alcohol and smoking, while adenocarcinoma is related to higher body mass index, white race and Barrett's esophagus.
Keywords: Esophageal Neoplasms; Carcinoma, Squamous Cell; Adenocarcinoma; Epidemiology